Republic of India : Service Level Benchmarking, Citizen Voice and Performance Improvement Strategies in Urban Water Supply and Sanitation - World Bank Group (World Bank, Washington, DC, 2016)
This synthesis report details the process, outputs and intermediate outcomes of the Water and Sanitation Program - World Bank (WSP) Technical Assistance (TA) to Service Level Benchmarking, Citizen Voice and Performance Improvement Strategies in Urban Water Supply and Sanitation (UWSS) in India. This technical assistance (TA) sought to strengthen accountability for service outcomes in urban water and sanitation, by providing support for strengthening (i) supply and demand side monitoring processes under national programs, and (ii) integrating use of performance data into decision making by public providers in select states, with specific focus on services to the poor. This TA was a continuation of WSP’s past technical assistance to the Ministry of Urban Development (MoUD) on adoption of benchmarking and accountability processes for the urban water supply and sanitation sector. During the period 2008-12, WSP had extended support to MoUD for development of the Handbook on Service Level Benchmarks (SLB), implementation of a national pilot followed by its rollout across the country. This TA was designed to provide follow up support for deepening of these performance monitoring and reporting processes, and activate demand side monitoring mechanisms to strengthen accountability. This TA has contributed to the following outcomes: (a) Demonstrated an innovative approach for ICT-based citizen feedback processes (“SLB Connect”) which has been leveraged for conduct of city level ratings under a national urban program, informed preparation of city level service improvement plans, and been integrated in the design of a Bank funded project. (b) Strengthened use of performance data for planning and investment processes in one state including development of a prioritization framework to guide allocations. (c) Supported analytical work and advocacy for strengthening of performance monitoring processes at the national and state levels. Going forward, in the Indian context, it would be important to operationalize the National Performance Monitoring Cell (NPMC) at the earliest, so that it can further strengthen performance monitoring processes in the sector.